2021
DOI: 10.20885/jaai.vol25.iss1.art2
|View full text |Cite
|
Sign up to set email alerts
|

Is there any interaction between real earnings management and accrual-based earnings management?

Abstract: This research aims to investigate whether firms employ real earnings management (REM) and accrual-based earnings management (AEM) as substitutes for each other when managing earnings to meet earnings benchmarks. It specifically looks at the sequential nature of both forms of earnings management. REM is proxied by an abnormal amount of operating cash developed by Dechow et al. (1998), while AEM is proxied by the discretionary accrual model by Dechow, Sloan, & Sweeney (1995). The data was obtained from the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
2
2
0
1
Order By: Relevance
“…The outcome of the study revealed that sustainability reporting has negative effects on both, discretionary accrual and real earnings management. The findings of this study are in agreement with the research conducted by Vogy (2021), which explored the most effective measure of earnings management. According to Vogy (2021), firms use both forms of earnings management in a sequential manner, with managers resorting to accrual-based earnings management more frequently if earnings produced through real manipulations fail to meet the earnings target.…”
Section: Conclusion and Recommendationsupporting
confidence: 90%
See 2 more Smart Citations
“…The outcome of the study revealed that sustainability reporting has negative effects on both, discretionary accrual and real earnings management. The findings of this study are in agreement with the research conducted by Vogy (2021), which explored the most effective measure of earnings management. According to Vogy (2021), firms use both forms of earnings management in a sequential manner, with managers resorting to accrual-based earnings management more frequently if earnings produced through real manipulations fail to meet the earnings target.…”
Section: Conclusion and Recommendationsupporting
confidence: 90%
“…The findings of this study are in agreement with the research conducted by Vogy (2021), which explored the most effective measure of earnings management. According to Vogy (2021), firms use both forms of earnings management in a sequential manner, with managers resorting to accrual-based earnings management more frequently if earnings produced through real manipulations fail to meet the earnings target. Vogy (2021) further revealed that DAE and REM usually occur sequentially instead of simultaneously.…”
Section: Conclusion and Recommendationsupporting
confidence: 90%
See 1 more Smart Citation
“…Apart from these two theories, another theory used in research is positive accounting theory (Buanaputra, 2021;PE Setiawan & Dwiana Putra, 2019;Nadhifah & Arif, 2020;Meita, 2019) which explains the theory developed by explaining accounting policies and practice in the company and predict what policies will be chosen by managers under certain conditions in the future. Determination of appropriate accounting policies and practices is important for companies in terms of preparing financial reports.…”
Section: Methodsmentioning
confidence: 99%
“…Variabel dependen dalam penelitian ini adalah manajemen laba riil. Manajemen laba riil diukur dengan menggunakan model yang sesuai dengan penelitian sebelumnya (Buanaputra, 2021;Roychowdhury, 2006) = perubahan penjualan bersih perusahaan i pada periode ke-t-1. 𝐴 𝑡−1 = total aset perusahaan i pada periode ke-t-1.…”
Section: Variabel Dependenunclassified